2020
DOI: 10.1111/ijcs.12589
|View full text |Cite
|
Sign up to set email alerts
|

Colour effects in green advertising

Abstract: Starbucks and Whole Foods Market, known for eco-friendliness, signal their sustainability using a green logo as a particularly strong signal indicating socially desirable business practices (e.g., Mazar & Zhong, 2010; Yoon & Oh, 2016). Ironically, however, BP, infamous for the deadly and destructive Deepwater Horizon oil spill in the Gulf of Mexico, adopted a green label to counter the damage to the brand. Does the use of green to advertise environmental friendliness actually enhance advertising effectiveness?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 61 publications
1
49
0
Order By: Relevance
“…For example, Lim et al. (2020) found that different colour have different effect on green advertising. Specifically, compared with grey, green symbolizes eco‐friendliness and is more effective in producing positive attitudes towards the ads.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For example, Lim et al. (2020) found that different colour have different effect on green advertising. Specifically, compared with grey, green symbolizes eco‐friendliness and is more effective in producing positive attitudes towards the ads.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…It is also known that visual imagery is an effective way to inform consumers and capture their interest, but also to increase the perceived product benefits [ 69 ]. Furthermore, the image linked to the mountain pasture cheese message used in this study was predominated by the colour green, which has been demonstrated to be associated with environmental friendliness and is the most effective for producing positive attitudes [ 70 ]. Previous studies that have examined consumer perception on verbal versus pictorial claims reached opposite conclusions on which modality is most effective [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with extant research (Lang et al, 2002;Lang, 2017), structural factors of in-app ads refer to elements used to present information in-app ads. Based on related research from traditional online advertising we know that the in-app ad structure is assessed based on various structural factors such as animation (Cheung et al, 2017;Li et al, 2016;Liu et al, 2019;Muñoz-Leiva et al, 2018;Seo et al, 2018), color brightness (Chiu et al, 2017;Kareklas et al, 2019;Lim et al, 2020;Moore et al, 2005), location prominence (Al-Natour et al, 2013;Calisir and Karaali, 2008;Das tan et al, 2018;Li et al, 2016) and the size (Cho, 2003;Namin et al, 2020;North and Ficorilli, 2017). The structural perceptions are furthermore determined by the similarity to the background structure of the in-app ad, which refers to the relationship of an in-app ad to its background within the app.…”
Section: Previous Research On Structural and Semantic Factorsmentioning
confidence: 99%